Reading Comprehension by using Assemblr for Young Learner in 6th Grade Students of SDIT AL Irsyad - -, Hilman; Umalihayati; Abdul Muin Bahaf; Nia Kurniawati; Nuraeni; Dewi Setya Ningrum; Fakhira Anisa Maharani; Putri Solihatunnisa (Loquen, 2023)
This study aims to (1) analyze students' reading comprehension using Assemblr media; (2) find out whether this media can foster students' interest in reading. The approach in this research is descriptive qualitative, the subject of this research is 17 students of the 6th grade students of SDIT Al Irsyad Banten. Data were obtained from tests, questionnaires, and interviews. In the learning process, Assemblr is used as a medium or tool for displaying teaching materials. This teaching material is in the form of a story entitled "The Lonely Lion". The reading comprehension activity lasts for 15 minutes. After that, students were given 5 questions related to the contents of the story to find out students understanding. The results showed that reading comprehension was quite good with an average score of 84, and the results of the questionnaire showed 64.7% of students found using Assemblr learning media more fun and growing their interest and motivation in reading. Based on the results of the study, it was concluded that Assemblr can make learning activities interactive and fun with 3D and AR.